Koherensi Kebijakan dan Perencanaan Kota Berkelanjutan: Studi Kasus RDTR Kota Palu - Herman, Sitti Rabiatul Wahdaniyah; Takwim, Supriadi; A, Rasdiana; Hadid, Adina Khusnudzan; Halim, Muhammad Adhim (Jurnal Peweka Tadulako, 2025)
Sustainable urban development requires alignment between national policies, local spatial planning, and commitments to global agendas. Palu City, as a growth center in Central Sulawesi and an area with high disaster vulnerability, needs a Detailed Spatial Plan (RDTR) that not only regulates land use but also integrates principles of sustainability and disaster resilience. This study aims to assess the extent to which Palu City’s RDTR aligns with Law No. 11 of 2020 on Job Creation, Government Regulation No. 21 of 2021 on Spatial Planning Implementation, and Sustainable Development Goal (SDG) 11. This research employed a document-based literature review, analyzing relevant regulations, the RDTR document, and academic literature. The evaluation was conducted using a policy coherence framework to examine internal, vertical, and horizontal consistency. The findings reveal that Palu City’s RDTR demonstrates strong internal consistency, with clear integration between objectives, strategies, and regulatory instruments. Vertically, it aligns with the national legal framework, particularly in zoning, protection of conservation areas, and land-use control. Horizontally, it contributes to several SDG 11 targets, including safe and affordable transportation access, disaster risk reduction, and the provision of green public spaces. However, disaster mitigation integration lacks measurable indicators, cross-sectoral synergy remains limited, and public participation needs to be extended to the implementation stage. Strengthening multi-hazard risk mapping, adopting inclusive cross-sectoral strategies, and establishing sustainable public participation mechanisms are recommended to make Palu City’s RDTR more adaptive, responsive, and aligned with sustainable development principles.